Development of a cross-cultural scale on attitudes toward gender and sexual diversity (AGSD) - Oleas, Daniel; Garza-Olivares, Xochitl; Teixeira-Filho, Fernando Silva; Mascialino, Guido; Rodas, Jose A. (Frontiers in Sociology, 2025)
BackgroundAttitudes toward gender and sexual diversity can range from acceptance to rejection, influenced by various social, psychological, and cultural factors. In Latin America, instruments tailored to measure these attitudes within specific cultural contexts are limited. This study aimed to develop and validate a culturally relevant scale to assess attitudes toward gender and sexual diversity in Ecuador.MethodsThe research was conducted in two studies. In Study 1, an exploratory factor analysis (EFA) was performed on data collected from 225 psychology students to identify the scale's structure. In Study 2, a confirmatory factor analysis (CFA) was conducted with 362 students to confirm the factor structure and assess the scale's validity. The final scale comprised 18 items across three factors: social coexistence, moral and pathological views, and stereotypes.ResultsThe scale demonstrated sound psychometric properties, with acceptable internal consistency (Cronbach's α = 0.74–0.77). Factor loadings ranged from 0.56 to 0.87, confirming the robustness of the scale. Three distinct factors were identified, providing a comprehensive measure of attitudes toward gender and sexual diversity in social, psychological, and behavioral contexts.ConclusionThis scale represents a valuable tool for assessing attitudes toward gender and sexual diversity in Latin American populations. Future research should test its applicability across broader populations and in different Latin American countries to further validate its use and generalizability.